Marek’s disease virus-specific T cells proliferate, express antiviral cytokines but have impaired degranulation response - Boodhoo, Nitish; Behboudi, Shahriar (Frontiers in Immunology, 2022)
The major histocompatibility complex (MHC) haplotype is one of the major determinants of genetic resistance and susceptibility of chickens to Marek’s disease (MD) which is caused by an oncogenic herpesvirus; Marek’s disease virus (MDV). To determine differential functional abilities of T cells associated with resistance and susceptibility to MD, we identified immunodominant CD4+TCRvbeta1 T cell epitopes within the pp38 antigen of MDV in B19 and B21 MHC haplotype chickens using an ex vivo ELISPOT assay for chicken IFN-gamma. These novel pp38 peptides were used to characterize differential functional abilities of T cells as associated with resistance and susceptibility to MD. The results demonstrated an upregulation of cytokines (IL-2, IL-4, IL-10) and lymphocyte lysis-related genes (perforin and granzyme B) in an antigen specific manner using RT-PCR. In the MD-resistant chickens (B21 MHC haplotype), antigen-specific and non-specific response was highly skewed towards Th2 response as defined by higher levels of IL-4 expression as well as lymphocyte lysis-related genes compared to that in the MD-susceptible chicken line (B19 MHC haplotype). Using CD107a degranulation assay, the results showed that MDV infection impairs cytotoxic function of T cells regardless of their genetic background. Taken together, the data demonstrate an association between type of T cell response to pp38 and resistance to the disease and will shed light on our understanding of immune response to this oncogenic herpesvirus and failure to induce sterile immunity.